Effectiveness of Education Programs About Oral Antibiotic Suspensions in Pediatric Outpatient Services - Hsin Hu; Fe-Lin Lin Wu; Fu-Chang Hu; Hui-Yuan Yang; Shu-Wen Lin; Li-Jiuan Shen (Pediatrics and Neonatology)
The effectiveness of education programs for pediatric patients receiving oral antibiotic suspension was unclear. Methods: When pediatric patients were prescribed antibiotics in powder form for suspension at the outpatient clinic of a university hospital, the responsible 150 caregivers were consecutively allocated into three education programs: Group 1 subjects read the package insert; Group 2 read a photograph-designed educational sheet; and Group 3 received a face-to-face medication education from a pharmacist with the photograph-designed educational sheet. The effectiveness of the three education programs for pediatric patients' caregivers was evaluated using a questionnaire comprised of 12 questions. Results: The proportions of the caregivers in Groups 1, 2 and 3 who answered the questionnaire perfectly with 100% accuracy were 2%, 14% and 74%, respectively (p<0.001). The means±standard deviations of the overall time spent by the caregivers in Groups 1, 2 and 3 were 353±135, 334.2±115.1, and 281.4±114 seconds, respectively (p=0.013). Clearly, the pharmacist's face-to-face mediation education program provided effective and time-saving medication instructions for pediatric oral antibiotics. The specific questions regarding easy-to-make errors related to the reconstitution step (p<0.001), water volume for reconstitution (p<0.001), storage temperature (p=0.004) and shelf life (p=0.002) of stock powder, whether the drug should be taken before or after a meal (p<0.001), and the method and volume for syrup measurement (p<0.001). Conclusion: This study demonstrated that when compared to reading a package insert or education sheet, a pharmacist's verbal education with photographic education materials was significantly more effective and time-saving in providing caregivers with the correct knowledge of oral antibiotic suspensions in pediatrics.